2016
DOI: 10.1002/jcla.22010
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk and Serum Hyaluronic Acid: A Preliminary Study in a Healthy Population of Low/Intermediate Risk

Abstract: Serum HA should be explored as an early marker of atheromatosis and cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…A significant positive correlation was found between HA levels and glycemia in our study population. Our findings were in line with previous studies, also reporting a critical role for HA in DM-related atherosclerosis ( 26 29 , 65 ). In vascular dysfunction, HA triggers smooth muscle cells’ dedifferentiation, which contributes to vessel wall thickening.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A significant positive correlation was found between HA levels and glycemia in our study population. Our findings were in line with previous studies, also reporting a critical role for HA in DM-related atherosclerosis ( 26 29 , 65 ). In vascular dysfunction, HA triggers smooth muscle cells’ dedifferentiation, which contributes to vessel wall thickening.…”
Section: Discussionsupporting
confidence: 94%
“…Hyaluronan (HA) is present in low amount in normal blood vessels but increases in vascular diseases as well as in DM ( 25 ). It seems to have an important role in diabetic angiopathy ( 26 28 ) and is associated with an increased risk for developing CAD also in non-diabetic patients ( 29 ). HA is increased in vascular plaques, and its high metabolism causes their destabilization ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we provide evidence that serum levels of HA at stable state were significantly associated with time to death independently of adjusted Charlson score, annual exacerbation rate and BODE index components. It has been shown that HA serum levels are elevated in patients with dyslipidaemia and high cardiovascular risk [26]. In our study, patients included in the validation cohort had numerous comorbidities, including arterial hypertension and coronary arterial disease.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, in vitro data suggests that CXCL4 may interact with gp120 to prevent HIV-1 infection of CD4 + T lymphocytes [ 19 , 20 ]. HA is an extracellular matrix component produced during wound healing, and circulating concentrations are increased in fibrotic diseases [ 13 , 21 23 ]. In HIV infection, HA has been associated with a 4.6-fold increased risk of death or AIDS diagnosis, and an 8.7-fold increased risk of immune reconstitution inflammatory syndrome within twelve months of ART initiation [ 24 ].…”
Section: Introductionmentioning
confidence: 99%